Kualitas Diet sebagai Faktor Penentu Status Gizi pada Remaja di SMAN 2 Bogor: Diet Quality as a Key Determinant of Adolescents Nutritional Status at SMAN 2 Bogor - Putri, Nabila Alifia; Marjan, Avliya Quratul; Imrar, Iin Fatmawati (Universitas Airlangga, 2025)
Background: One of the causes of nutritional problems in adolescents is an imbalance in food intake, which can be evaluated by diet quality. Objectives: This study aims to assess the quality of diet as one of the important determinants associated with the nutritional status of adolescents at SMAN 2 Bogor. Methods: This study employed an analytical observational cross-sectional design involving 103 students aged 16-18 years. Dietary quality was assessed using a 2×24-Hour Food Recall and analyzed with the Diet Quality Index for Adolescents (DQI-A), modified based on the 2014 Balanced Nutrition Guidelines. Bivariate analysis employed the Spearman test, and differences in diet quality scores were examined using the Mann-Whitney test. Results: Diet Quality Index (DQI) results indicate that 50.5% of respondents had good dietary quality. The average dietary quality score of the respondents was 37.5%, with a score range of 9.86% to 66.36%. Several respondents exhibited poor diet quality due to high-energy, low-nutrient food intake. Most respondents consumed 4-5 of the 7 recommended food groups and less than the recommended portion sizes. No significant difference was found between diet quality on school days and weekends (p-value>0.05). Diet quality was significantly associated with adolescents' nutritional status at SMAN 2 Bogor with p-value<0.001. Conclusions: This study demonstrates that diet quality is a crucial factor in determining the nutritional status of adolescents. Adolescents should prioritise the quality of their diet in terms of food quality, diversity, and balance.